Elucidating the Role of Hydroxide Electrolyte on Anion-Exchange-Membrane Water Electrolyzer Performance. Issue 5 (19th May 2021) - Liu, Jiangjin; Kang, Zhenye; Li, Dongguo; Pak, Magnolia; Alia, Shaun M.; Fujimoto, Cy; Bender, Guido; Kim, Yu Seung; Weber, Adam Z.
Abstract : Many solid-state devices, especially those requiring anion conduction, often add a supporting electrolyte to enable efficient operation. The prototypical case is that of anion-exchange-membrane water electrolyzers (AEMWEs), where addition of an alkali metal solution improves performance. However, the specific mechanism of this performance improvement is currently unknown. This work investigates the functionality of the alkali metal solution in AEMWEs using experiments and mathematical models. The results show that additional hydroxide plays a key role not only in ohmic resistance of the membrane and catalyst layer but also in the reaction kinetics. The modeling suggests that the added liquid electrolyte creates an additional electrochemical interface with the electrocatalyst that provides ion-transport pathways and distributes product gas bubbles; the total effective electrochemical active surface area in the cell with 1 M KOH is 5 times higher than that of the cell with DI water. In the cell with 1 M KOH, more than 80% of the reaction current is associate with the liquid electrolyte. These results indicate the importance of high pH of electrolyte and catalyst/electrolyte interface in AEMWEs. The understanding of the functionality of the alkali metal solution presented in this study should help guide the design and optimization of AEMWEs.